2021
DOI: 10.3390/vetsci8080152
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Implications of Detoxified Jatropha curcas Kernel for Clarias gariepinus Fingerlings

Abstract: Antinutritional components must be substantially reduced to ensure better utilization of unconventional feeds in animal nutrition. Among the different methods of processing, soaking represents a simple and inexpensive alternative. This study attempted to determine the nutritional properties of socked Jatropha curcas kernel (JCK) and the effect of its dietary inclusions on Clarias gariepinus (n = 50; mean initial weight = 6.19 ± 0.52 g). Three treatments of JCK (i.e., soaking 24, 48, and 72 h) were tested along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Other anti-nutrients in the cake include phytate, trypsin inhibitor, lectin and saponin (Phengnuam and Suntornsuk, 2013). All the listed toxic substances and the antinutrients could be removed by proper processing methods such as chemical extraction, solid-state fermentation, heating, soaking and so on (Saetae and Suntornsuk, 2011, Sanusi et al, 2013, Gogoi et al, 2014, Okomoda et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other anti-nutrients in the cake include phytate, trypsin inhibitor, lectin and saponin (Phengnuam and Suntornsuk, 2013). All the listed toxic substances and the antinutrients could be removed by proper processing methods such as chemical extraction, solid-state fermentation, heating, soaking and so on (Saetae and Suntornsuk, 2011, Sanusi et al, 2013, Gogoi et al, 2014, Okomoda et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…However, the experimental sh was Labeo rohita. Okomoda et al (2021) used African cat sh as experimental sh, but they chose to soak Jatropha curcas at various time intervals to detoxify the cake. Although the authors reported their observations on the growth performance, histology and haematology of the fed sh, there was no report on the enzyme activities and serum biochemistry of the fed sh.…”
Section: Introductionmentioning
confidence: 99%